Postradioiodine Graves' management: The PRAGMA study. (21st March 2022) - Perros, Petros; Basu, Ansu; Boelaert, Kristien; Dayan, Colin; Vaidya, Bijay; Williams, Graham R.; Lazarus, John H.; Hickey, Janis; Drake, William M.; Crown, Anna; Orme, Stephen M.; Johnson, Andrew; et al.
Abstract: Objective: Thyroid status in the months following radioiodine (RI) treatment for Graves' disease can be unstable. Our objective was to quantify frequency of abnormal thyroid function post‐RI and compare effectiveness of common management strategies. Design: Retrospective, multicentre and observational study. Patients: Adult patients with Graves' disease treated with RI with 12 months' follow‐up. Measurements: Euthyroidism was defined as both serum thyrotropin (thyroid‐stimulating hormone [TSH]) and free thyroxine (FT4) within their reference ranges or, when only one was available, it was within its reference range; hypothyroidism as TSH ≥ 10 mU/L, or subnormal FT4 regardless of TSH; hyperthyroidism as TSH below and FT4 above their reference ranges; dysthyroidism as the sum of hypo‐ and hyperthyroidism; subclinical hypothyroidism as normal FT4 and TSH between the upper limit of normal and <10 mU/L; and subclinical hyperthyroidism as low TSH and normal FT4. Results: Of 812 patients studied post‐RI, hypothyroidism occurred in 80.7% and hyperthyroidism in 48.6% of patients. Three principal post‐RI management strategies were employed: (a) antithyroid drugs alone, (b) levothyroxine alone, and (c) combination of the two. Differences among these were small. Adherence to national guidelines regarding monitoring thyroid function in the first 6 months was low (21.4%–28.7%). No negative outcomes (new‐onset/exacerbation of Graves' orbitopathy, weight gain, and cardiovascular events) were associated with dysthyroidism. There were significant differences in demographics, clinical practice, and thyroid status postradioiodine between centres. Conclusions: Dysthyroidism in the 12 months post‐RI was common. Differences between post‐RI strategies were small, suggesting these interventions alone are unlikely to address the high frequency of dysthyroidism.